2016
DOI: 10.21462/jeltl.v1i3.29
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Affecting Successful Integration of ICT in Moroccan Universities

Abstract: The implementation of technology in classrooms affords educators more opportunities to work better in their lessons. However, there are numerous distinctive barriers that might prevent teachers from making use of Information and Communication Technology (ICT) in their teaching practices. Admittedly, studying the obstacles to the integration of technology in schools would be an important step in developing the quality of teaching. The primary objective of this study is to discover the barriers that stop univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…According to teachers' technology skills and knowledge, results confirmed that more than half of teachers feel less competent to use ICT, as had been indicated in previous studies [27]. Teachers' technology skills and knowledge is among the most dominant obstacles to distance teaching.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 82%
“…According to teachers' technology skills and knowledge, results confirmed that more than half of teachers feel less competent to use ICT, as had been indicated in previous studies [27]. Teachers' technology skills and knowledge is among the most dominant obstacles to distance teaching.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 82%
“…Teachers are often overwhelmed by heavy teaching loads which do not make provision for training opportunities (Sabaliauskas, Ghavifekr et al, 2016). According to Laabidi and Laabidi (2016), there is a critical need to enhance professional competence of teachers through skills training to ensure that learners are adequately prepared for a technological society. Teachers who have little or no confidence to apply technologies in their occupation will try to escape from those occupations altogether (Laabidi & Laabidi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Laabidi and Laabidi (2016), there is a critical need to enhance professional competence of teachers through skills training to ensure that learners are adequately prepared for a technological society. Teachers who have little or no confidence to apply technologies in their occupation will try to escape from those occupations altogether (Laabidi & Laabidi, 2016). The teachers acknowledged the fact that learners were more knowledgeable than them when it comes to technology use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the researchers had reservations about the little research on the demerits of infusion of technology in learning Arabic. Laabidi and Laabidi (2016) examined challenges faced in infusing ICT in TAFL and found a shortage of research studies that examined hurdles faced in the use of ICT in instructing and learning foreign languages. Omari (2015) also examined computer-aided techniques in instruction and learning of Arabic using a mixed design and found that the permeation of pedagogy compels teachers to assimilate technology in their instruction.…”
Section: Role Of Technology In Teaching and Learning Aslmentioning
confidence: 99%